Enantiomeric Selection Properties of β‐homoDNA: Enhanced Pairing for Heterochiral Complexes1. Issue 26 (13th May 2013) - D'Alonzo, Daniele; Amato, Jussara; Schepers, Guy; Froeyen, Matheus; Van Aerschot, Arthur; Herdewijn, Piet; Guaragna, Annalisa
<x xml:space="preserve">Abstract</x> De gustibus: β‐homoDNA has the singular property of being able to pair with homochiral complements of opposite chirality, with a greater stability than that observed in the corresponding isochiral complexes. Relevant to etiological investigations on nucleic acid structure, these results suggest the existence of a relationship between carbohydrate structure and stereoselectivity of the hybridization processes of the corresponding nucleic acids.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>